Fundamentals of decentralized clinical trials strategy and execution - Yang, Anna H. (Springer, 2024)
A timely and first-of-its-kind publication in the field, this short handbook on decentralized clinical trials (DCTs) offers a thorough exploration of the potential of DCTs to revolutionize clinical research through innovative approaches, including technology. This concise and easy-to-read publication is especially designed for those who seek to understand and get up-to-speed on what DCTs mean and how to work in this rapidly evolving field. As discussed in Chapter 1, DCTs address barriers to traditional trial participation, promoting accessibility, diversity, equity, and participant engagement. Chapter 2 examines how the COVID-19 pandemic and evolving regulations accelerated the adoption of DCTs, building on their application since the early 2000s. Chapters 3 and 4 highlight remaining operational complexities and the importance of careful trial design to ensure scientific rigor, operational feasibility, and compliance with regulations, ethics, data privacy, and participant safety. The book emphasizes the significance of the FDA's draft guidance on DCTs, detailing investigator responsibilities, local health care providers' use, and essential sponsor considerations. Chapter 5 stresses the need for clear metrics to evaluate DCT adoption's impact on recruitment, retention, diversity, safety, and cost efficiencies. Overall, this guide tracks DCT advancements and encourages readers to contribute to evidence-based integration, meeting participant expectations for convenience and fostering faster, more inclusive clinical studies. Ultimately, this book aims to support the transformation of modern clinical research, developing medical products more efficiently for those in need. A major contribution to the literature on clinical research, this work will be a resourceful tool to anyone interested in embracing decentralized clinical research and improving access and participation for all